2020
DOI: 10.1002/adom.201901735
|View full text |Cite
|
Sign up to set email alerts
|

Solution‐Processed High‐Quality Cesium Lead Bromine Perovskite Photodetectors with High Detectivity for Application in Visible Light Communication

Abstract: devices in VLC are essential because their response speed, detectivity (D*), and stability determine the quality and speed of the signal acceptance. All-inorganic perovskites are very attractive for their application in the PDs with requirements of high durability, wide-range spectral responses, ultra-high D*, and fast response speed, due to their merits of high thermal stability, tunable bandgaps, high light absorption coefficients, and long carrier diffusion lengths. [2][3][4][5] Particularly, cesium lead br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 39 publications
0
39
0
Order By: Relevance
“…To investigate the potential of MHP PDs to the OWC, some groups simulated the core optocoupler of an OWC system, which consists of a signal generator, driving a light source (e.g., LED) to turn on and off quickly and an MHP PD connecting to a rapid oscilloscope, as shown in Figure 14a. [120,[309][310][311][312] Gao's group first integrated MHP PDs into an OWC system as an optical signal receiver on transmitting text and audio signals. [309] Li et al demonstrated MAPbI 3 PDs applied in a VLC system.…”
Section: Pds For the Optical Communicationmentioning
confidence: 99%
“…To investigate the potential of MHP PDs to the OWC, some groups simulated the core optocoupler of an OWC system, which consists of a signal generator, driving a light source (e.g., LED) to turn on and off quickly and an MHP PD connecting to a rapid oscilloscope, as shown in Figure 14a. [120,[309][310][311][312] Gao's group first integrated MHP PDs into an OWC system as an optical signal receiver on transmitting text and audio signals. [309] Li et al demonstrated MAPbI 3 PDs applied in a VLC system.…”
Section: Pds For the Optical Communicationmentioning
confidence: 99%
“…Nevertheless, the low solubility of CsX in precursor solution gave rise to discontinuous and porous films, hindering the final product. [ 122 ] In the preparation of bulk film, trace impurities were a common problem, which necessitate more research efforts in the future.…”
Section: Direct Synthesis Of Low‐dimensional‐networked Perovskitesmentioning
confidence: 99%
“…[ 197 ] Benefiting from the deposition method, the compositions and thickness of the films could be precisely controlled by varying the CsBr/PbBr 2 ratio and dosage. Recently, a solution deposition coating [ 122 ] and a post‐treatment method [ 198 ] have been developed in the synthesis of CsPbBr 3 /CsPb 2 Br 5 composite films. In these films, the presence of wide bandgap semiconductor CsPb 2 Br 5 provided significant self‐passivation at the interface, which was believed to have reduced the charge recombination in CsPbBr 3 .…”
Section: Hybridization Of Low‐dimensional‐networked Perovskitesmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, lead halide perovskite nanocrystals, APbX 3 (A = CH 3 NH 3 + (MA + ), NH 2 HCNH 2 + (FA + ), and Cs + , X = Cl, Br, and I) have attracted great interest and been widely used in solar cells, [ 1,2 ] lasers, [ 3,4 ] light‐emitting diodes (LEDs), [ 5,6 ] bioimaging [ 7 ] and photodetectors [ 8,9 ] due to their broad excitation, narrow‐band emission (full width at half‐maximum (FWHM) of 12–42 nm), [ 10,11 ] tunable wavelength (400–700 nm), [ 12‐14 ] high photoluminescence quantum yield ( PLQY ≈ 100%), [ 15,16 ] direct bandgap, [ 17 ] defect tolerance, [ 18 ] long diffusion length, [ 19,20 ] high carrier mobility, [ 21 ] and long carrier lifetime. [ 22,23 ] Especially, lead halide perovskite nanocrystals are suitable for solid‐state lighting and high‐definition display applications due to their wide color gamut ( NTSC ≈ 140%), [ 24,25 ] high color purity, [ 26 ] as well as facile synthesis methods.…”
Section: Introductionmentioning
confidence: 99%